A new bioactive cocrystal of coumarin‐3‐carboxylic acid and thiourea: detailed structural features and biological activity studies. Issue 3 (16th February 2022) - Shahbaz, Muhammad; Khan, Umair Ahmed; Chaudhary, M. Iqbal; Yousuf, Sammer
Abstract : A new cocrystal of coumarin‐3‐carboxylic acid and thiourea has been successfully obtained via a neat grinding method in a 1:1 stoichiometric ratio. An evaluation of the biological activity of the cocrystal revealed that it is a potent and noncytotoxic DPPH radical scavenger and therefore a potential candidate to explore further for its antioxidant properties. Abstract : Cocrystallization is a phenomenon widely used to enhance the biological and physicochemical properties of active pharmaceutical ingredients (APIs). The present study deals with the synthesis of a cocrystal of coumarin‐3‐carboxylic acid (2‐oxochromene‐3‐carboxylic acid, C10 H6 O4 ), a synthetic analogue of the naturally occurring antioxidant coumarin, with thiourea (CH4 N2 S) using the neat grinding method. The purity and homogeneity of the coumarin‐3‐carboxylic acid–thiourea (1/1) cocrystal was confirmed by single‐crystal X‐ray diffraction, FT–IR analysis and thermal stability studies based on differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Detailed geometry analysis via density functional theory (DFT) demonstrated that the 1:1 cocrystal stoichiometry is sustained by N—H…O hydrogen bonding between the amine (–NH2 ) groups of thiourea and the carbonyl group of coumarin. The synthesized cocrystal exhibited potent antioxidant activity (IC50 = 127.9 ± 5.95 µ M ) in a DPPH radical scavenger assay in vitro in comparison with the standard N ‐acetyl‐l ‐cysteine (IC50 = 111.6 ± 2.4 µ M ). The promising results of the present study highlight the significance of cocrystallization as a crystal engineering tool to improve the efficacy of pharmaceutical ingredients.